2004
DOI: 10.1029/2004gl020331
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of remote sensing of thin current sheet

Abstract: [1] Cluster encountered a thin current sheet in the magnetotail during a substorm on Oct. 1, 2001. The phase space distributions observed by Cluster CIS showed large gradients in the phase space with ions existing only in one hemisphere of the phase space. It has been suggested that these non-gyrotropic distributions come from remote sensing of a thin current sheet by spacecrafts outside the current sheet. We present the results of a test particle simulation that confirm non-gyrotropic distributions can arise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 18 publications
5
32
0
1
Order By: Relevance
“…The physical mechanism we propose to explain the crescent-shaped VDFs is based on finite Larmor radius effects. To our knowledge, this is for the first time when such kind of electron velocity distributions 20 are emphasized in the absence of X-lines and magnetic field reversal and the physical process proposed adds to the ones discussed in the past like, for instance, the remote sensing of a thin Harris sheet (Lee et al, 2004;, the dynamics of non-magnetized Speiser-like electrons (Bessho et al, 2016;Shay et al, 2016;Lapenta et al, 2017) or the dynamics of magnetized electrons (Egedal et al, 2016) in the diffusion region of magnetic reconnection sites.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The physical mechanism we propose to explain the crescent-shaped VDFs is based on finite Larmor radius effects. To our knowledge, this is for the first time when such kind of electron velocity distributions 20 are emphasized in the absence of X-lines and magnetic field reversal and the physical process proposed adds to the ones discussed in the past like, for instance, the remote sensing of a thin Harris sheet (Lee et al, 2004;, the dynamics of non-magnetized Speiser-like electrons (Bessho et al, 2016;Shay et al, 2016;Lapenta et al, 2017) or the dynamics of magnetized electrons (Egedal et al, 2016) in the diffusion region of magnetic reconnection sites.…”
Section: Discussionmentioning
confidence: 75%
“…Crescent-like VDFs were observed for ions in the Earth's magnetotail, close to the neutral sheet and plasma sheet 15 boundary layer (e.g., Nakamura et al, 1991Nakamura et al, , 1992Wilber et al, 2004), as well as in the magnetosheath, close to the magnetopause (e.g., Marcucci et al, 2004). The crescent-shaped ion VDFs have been associated with various finite Larmor radius effects (e.g., Lee et al, 2004;Marcucci et al, 2004;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen [6] reported that if the flow speed of ions is used as the only criterion for high-speed flows, then when the distribution function deviates from the Maxwellian distribution, the effect of integration could yield high speeds even though there is no real bulk flow. In addition, Lee et al [7] showed that when particles are moving near a boundary, the integration effect could lead to a non-zero speed in some direction. Therefore, the distribution functions must be carefully studied when high-speed flow problems are studied.…”
Section: High-speed Flowing Plasma In the Plasma Sheetmentioning
confidence: 99%
“…In the third section we illustrate the numerical solutions obtained for a cloud/beam of protons injected into a non-uniform electromagnetic field; we discuss the physical mechanisms that can explain the simulation results and can contribute to the formation of ring-shaped and energy-dispersed structures at the edges of the proton cloud/beam; we also compare the simulation results with experimental data from Cluster in the terrestrial magnetotail. 7 The last section includes our summary and conclusions.…”
Section: Introductionmentioning
confidence: 99%